Generation of robust bispecific antibodies through fusion of single-domain antibodies on IgG scaffolds: a comprehensive comparison of formats. Issue 1 (31st December 2023) - Madsen, Andreas V.; Kristensen, Peter; Buell, Alexander K.; Goletz, Steffen
ABSTRACT: Bispecific antibodies (bsAbs) enable dual binding of different antigens with potential synergistic targeting effects and innovative therapeutic possibilities. The formation of bsAbs is, however, often dependent on complex engineering strategies with a high risk of antibody chain mispairing leading to contamination of the final product with incorrectly assembled antibody species. This study demonstrates formation of bsAbs in a generic and conceptually easy manner through fusion of single-domain antibodies (sdAbs) onto IgG scaffolds through flexible 10 amino acid linkers to form high-quality bsAbs with both binding functionalities intact and minimal product-related impurities. SdAbs are attractive fusion partners due to their small and monomeric nature combined with antigen-binding capabilities comparable to conventional human antibodies. By systematically comparing a comprehensive panel of symmetric αPD-L1×αHER2 antibodies, including reversely mirrored antigen specificities, we investigate how the molecular geometry affects production, stability, antigen binding and CD16a binding. SdAb fusion of the heavy chain was generally preferred over light chain fusion for promoting good expression and high biophysical stability as well as maintaining efficient binding to both antigens. We find that N-terminal sdAb fusion might sterically hinder antigen-binding to the Fv region of the IgG scaffold, whereas C-terminal fusion might disturb antigen-binding to the fused sdAb. Our work demonstrates a toolbox of complementary methods for in-depth analysis of key features, such as in-solution dual antigen binding, thermal stability, and aggregation propensity, to ensure high bsAb quality. These techniques can be executed at high-throughput and/or with very low material consumption and thus represent valuable tools for bsAb screening and development.